Institutional Dynamics of Organic Rice Farmer Groups in West Sumatra, Indonesia - Vonny Indah Mutiara; Ami Sukma Utami; zulvera zulvera; Ifdal Ifdal; yulistriani yulistriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Organic rice farming is one of the crucial strategies to ensure food security in West Sumatra. However, the development of organic rice farming in West Sumatra has not progressed significantly. Only a few farmer groups apply for organic re-certification from the Organic Certification Institute. This study aims to analyze the institutional structure of farmer groups that have successfully maintained organic rice farming systems by examining farmer characteristics, group norms and rules, and social and cultural factors that influence the sustainability of organic rice farming systems. The study was conducted in Lima Puluh Kota Regency, West Sumatra. Three farmer groups were selected based on their current status of organic rice certification. This study used a multidimensional approach encompassing social, cultural, and economic aspects to assess the sustainability of organic rice farming. Data collection was carried out through a focus group discussion. The result showed that, though farmers' groups are certified, only a few members are implementing an organic rice farming system. However, they are still involved in making compost, natural pesticides, weeding and harvesting. This finding indicates that the main strength of these groups lies in bottom-up institutionalization and internal belief in organic values. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero hungerSDG 12: Responsible consumption and productionSDG 10: Reduced InequalitiesSDG 17: Partnerships for the Goals